Testing the KAPS Model of Reading Comprehension in a Turkish Elementary School Context from Low Socioeconomic Background - Kasim Yildirim; Fatih Cetin Cetinkaya; Seyit Ates; Dudu Kaya; Timothy Rasinski (MDPI AG, 2020)
This correlational study aimed to explore the relations of background knowledge, automaticity (rate), prosody, and strategy use with reading comprehension (KAPS model of reading comprehension) in the written Turkish language context with 207 fourth grade students. Successful comprehension requires readers to make meaning out of what they read. Our KAPS model of reading comprehension hypothesizes relations of background knowledge, fluency components (rate and prosody), and strategy use with reading comprehension components (literal and deep) in the Turkish language and addresses the direct effects of these predictors on the reading comprehension of fourth grade students. The results showed that, whereas fluency and strategy use made statistically significant contributions to reading comprehension, background knowledge did not. Based on the results, the study affirms the importance of automaticity in word recognition, prosody, and comprehension strategies in contributing to reading comprehension in Turkish and, as such, should be given priority for literacy instruction in Turkish.